HUBUNGAN ANTARA KARAMBA JARING APUNG DENGAN JENIS MAKANAN YANG TERDAPAT PADA LAMBUNG IKAN ENDEMIK DI WADUK KOTO PANJANG, RIAU - Eni Sumiarsih; Otong Suhara Djunaedi; Yayat Dhahiyat; Zahidah Zahidah (Indonesian Journal of Applied Sciences, 2015)
AbstractIn the Koto Panjang Dam, Riau there are more than 1582fish floating cages present.  Fish feed spilled from the cage is believed to affect the diet of wild endemic fishes inhabit the dam. To understand the effect of the cage on the diet of the endemic, a study has been conducted on May to September 2013. There were 5 sampling sites, 2 sites located in the natural area that there is no cage (St 1Na and St2 Na) and the others (3 Ka, 4 Ka and 5 Ka) were in the area around the cage. Fishes were sampled hourly, for a 24 hour period and their stomach content was analyzed. Results shown that there were 31 species of endemic fishes such as Puntius schwanenfeldii, Macrones nemurus, Hampala bimaculata, Osteochillus hasselti, Rasbora vaillanti, Tynnichtys vaillanti, Ophiocephalus melanosoma, Chela oxygastroides, Cyclocheilichthys heteronema, Notopterus chilata, Puntius bramoidesandCyclocheilichtys apogon. Among these fishes, however, only P. schwanenfeldii that greatly affected by the presence of the aquaculture activities as the stomach of fish living around the cage was filled with fish feed pellets (more than 90%). The fish living in the area with no cage, however, filled with animal and plant remains. This fact indicates that the P.  schwanenfeldii is an opportunist fish that is able to change their diet into fish feed pellets. Based on data obtained, it can be concluded that the presence of fish floating cage aquaculture activities affect certain fish species only.Key words: Fish floating cage, Puntius schwanenfeldii, Koto Panjang Dam, endemic fish, fish feed pellet